اردو شعرو ادب پر فارسی کے اثرات:چند پہلو - Dr. Ali Bayat; Dr. Imran Zafar (Khayaban - خیابان, 2021)
Abstract: Just as the Indian Subcontinent accepted the effects of the Persian culture and civilization, in view of the geographical relations with its neighbor Iran, Urdu language and literature employed the Persian poetic tradition and language and literature as much as they could. The influence of Persian on Urdu language and literature is the proof that the ancestors of the young generation who speak and understand Urdu in the present times have benefited from Iranian culture and civilization, for centuries, a cultural spring that is one of the world's oldest and dominant civilizations. So they need to strengthen their relationship even more than ever. The existence of Persian words and dialects in Urdu language is the argument for undeniable collaborations between the people of the two regions and collaborations play a vital role in strengthening the relationships. Of course, the collaborations in The Indian Subcontinent and Iran are very wide. A manifestation of which is the existence of these collaborations in Urdu poetry and literature. Of course, study of these collaborations can be very pleasant and enjoyable. Abstract: Just as the Indian Subcontinent accepted the effects of the Persian culture and civilization, in view of the geographical relations with its neighbor Iran, Urdu language and literature employed the Persian poetic tradition and language and literature as much as they could. The influence of Persian on Urdu language and literature is the proof that the ancestors of the young generation who speak and understand Urdu in the present times have benefited from Iranian culture and civilization, for centuries, a cultural spring that is one of the world's oldest and dominant civilizations. So they need to strengthen their relationship even more than ever. The existence of Persian words and dialects in Urdu language is the argument for undeniable collaborations between the people of the two regions and collaborations play a vital role in strengthening the relationships. Of course, the collaborations in The Indian Subcontinent and Iran are very wide. A manifestation of which is the existence of these collaborations in Urdu poetry and literature. Of course, study of these collaborations can be very pleasant and enjoyable.